Cachectin/tumor necrosis factor-alpha formation in human decidua. Potential role of cytokines in infection-induced preterm labor. - Casey, M L; Cox, S M; Beutler, B; Milewich, L; MacDonald, P C (The Journal of Clinical Investigation, 1989)
This study was conducted as part of an investigation to evaluate the hypothesis that bacterial toxins (LPS or lipoteichoic acid), acting on macrophage-like uterine decidua to cause increased formation of cytokines, may be involved in the pathogenesis of infection-associated preterm labor. We found that cachectin/tumor necrosis factor-alpha (TNF-alpha) was synthesized and secreted into the culture medium by human decidual cells and explants in response to treatment with LPS. LPS treatment also caused an increase in PGF2 alpha production by decidual cells and explants. In amnion cells in monolayer culture, TNF-alpha stimulated PGE2 formation, and TNF-alpha was cytostatic (inhibited [3H]thymidine incorporation into DNA) but not cytolytic in amnion cells. TNF-alpha was not detectable (less than 0.34 ng/ml) in the amniotic fluid of normal pregnancies at midtrimester or at term before or after the onset of labor (n = 44); but TNF-alpha was present at concentrations between 2.8 and 22.3 ng/ml in amniotic fluids of 4 of 20 pregnancies with intact membranes complicated by preterm labor (less than 34 wk gestational age). LPS was present in 10 of the 20 amniotic fluids of preterm labor pregnancies, including all four in which TNF-alpha was present. Bacteria were identified in only one of the four LPS-positive, TNF-alpha-positive fluids. Cytokine formation in macrophage-like decidua may serve a fundamental role in the pathogenesis of preterm labor, including increased prostaglandin formation and premature rupture of the membranes. Images